The role of liquid–liquid phase separation in aggregation of the TDP-43 low-complexity domain - Babinchak, W. Michael (J Biol Chem, 2019)
Pathological aggregation of the transactive response DNA-binding protein of 43 kDa (TDP-43) is associated with several neurodegenerative disorders, including ALS, frontotemporal dementia, chronic traumatic encephalopathy, and Alzheimer's disease. TDP-43 aggregation appears to be largely driven by its low-complexity domain (LCD), which also has a high propensity to undergo liquid–liquid phase separation (LLPS). However, the mechanism of TDP-43 LCD pathological aggregation and, most importantly, the relationship between the aggregation process and LLPS remains largely unknown. Here, we show that amyloid formation by the LCD is controlled by electrostatic repulsion. We also demonstrate that the liquid droplet environment strongly accelerates LCD fibrillation and that its aggregation under LLPS conditions involves several distinct events, culminating in rapid assembly of fibrillar aggregates that emanate from within mature liquid droplets. These combined results strongly suggest that LLPS may play a major role in pathological TDP-43 aggregation, contributing to pathogenesis in neurodegenerative diseases.